PENINGKATAN PRODUKSI DAN KECERNAAN BAHAN KERING ALFALFA DENGAN PEMUPUKAN FOSFAT - - Sunarni; - Karno; Dwi Retno Lukiwati (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak)
Alfalfa (Medicago    sativa    L.) as one of legume forage crops for ruminant livestock is very sensitive to the phosphorus deficiency. Phosphorus fertilizers have been used widely to overcome those problem. However, the high cost of superphosphate (SP) is now focusing attention on cheaper rock phosphate (RP) fertilizer. A field experiment was conducted on a latosolic soil (low pH, and low available Bray II extractable P). The objective of the research is to evaluate the effect of phosphorus fertilizer from difference sources on dry matter production, and in    vitro dry matter digestibility of alfalfa. Completely randomized block design with 7 treatments in 3 replicates was used in this field experiment. The treatments were T0 (control), T1 (SP, 100 kg P2O5/ha), T2 (SP, 200 kg P2O5/ha), T3 (SP, 300 kg P2O5/ha), T4 (RP, 100 kg P2O5/ha), T5 (RP, 200 kg P2O5/ha), T6 (RP, 300 kg P2O5/ha). Size of each plot was 2 m x 2 m, and fertilized with P fertilizer (SP, RP) according to the assigned treatment. All plot received basal fertilizer of urea (50 kg N/ha), KCl (100 kg K2O/ha) and poultry manure (2 ton/ha). Medicago    sativa was defoliated on 12 weeks after planting and analyzed for dry matter (DM) production and in    vitro DM digestibility. Result showed that DM production significantly influenced by the treatments. Superphosphate fertilization resulted DM production significantly higher compared to control and RP, except on RP 300 kg P2O5/ha was non-significant difference. In    vitro dry matter digestibility (IVDMD) of alfalfa was not affected by the treatment. There was non-significant difference in IVDMD between the treatments. Therefore, RP (300 kg P2O5/ha) could replace SP to increased DM production and not affected for IVDMD of Medicago    sativa in acid latosolic soil.